Influence of availability of Information materials on the reading habits of senior secondary school students in Ijebu –Ode, Ogun State, Nigeria - Adesina, Odunola Ibiyemi; Madukoma, Ezinwanyi; Bamidele, Itunu Adeola (Communicate: Journal of Library and Information Science, 2025)
The ability to read and write is seen as one of the most important factors in a child’s education and development. The study investigates the contributing effect of information materials availability on the reading habits of senior secondary school students in Ijebu-Ode Local Government, Ogun State, Nigeria. Survey research design was adopted for the study. The population comprised 989 senior secondary school students in Ijebu-Ode, Ogun State, Nigeria. Simple random sampling was used to select 426 participants who formed the sample size for the study. A structured and validated questionnaire was used to collect data. Data analysis was done using descriptive and inferential (multiple regression) statistics. Findings of the study indicates that the reading habit of the respondents was good by the grand mean of (x̅=3.99), also the result reveals that all the information resources studied are available to the students; the finding also shows that the challenges studied can be seen to be on the average that affect the reading habit of students going by the grand mean of 2.76, also the result indicates that information materials availability has significant influence on the reading habits of senior secondary school students in Ijebu-Ode, Ogun State ((R2 = .272; F (2,423) =80.297, P<0.005). Based on the findings of the study, the following recommendations are made: schools should ensure regular update and expansion of their information materials to sustain students' interest in reading, teachers and librarians should organize reading competitions, book clubs, and other activities that promote reading habits among students.